Study of the process of shape-formation of ribbed double-curvature panels by local deforming - Sikulskiy, Valeriy; Kashcheyeva, Valentina; Romanenkov, Yuri; Shapoval, Alexander (Eastern-European Journal of Enterprise Technologies, 2017)
Accuracy of double-curvature ribbed panels obtained by multipoint local deformation using the proposed procedure of distribution of local actions was studied. As equipment for local action, an innovative die was used enabling the rib portion to be bent together with the adjacent sheet in both directions and perform shrinking (shortening) or stretching (extension) of this section along the rib axis. Features of making double-curvature panels with an irregular internal structure using local shaping by bending and shrinking (stretching) were considered. A procedure was described for calculating the number of local actions necessary to obtain panels of the required shape and size. The results obtained in testing the procedure for distributing local actions on samples and the full-scale panel of an aircraft fuselage of a transport category were presented. An experimental study of accuracy of the obtained dimensions by comparison of measurements of height of the points in the shaped panel with calculated values of the panel coordinates was carried out. Experimental studies of accuracy of the panel face shape showed that the maximum deviation after applying the calculated actions was 1.48 mm for longitudinal sections and 1.67 mm for transverse ones. Individual deviations of the shape, for example deviations of the free edges and curvature near the ends of the ribs required refinement works after which the shape deviations did not exceed 0.3 mm. Basic recommendations were elaborated for making double-curvature (biconvex, biconcave, convexo-concave and concavo-convex) panels.